The education values and motivation behind violence in the tradition of the Sasak Tribe in Indonesia - Zohdi, Ahmad; Ali, Lalu Usman; Ibrahim, Nurshahira (Department of Anthropology, Faculty of Social and Political Sciences, Hasanuddin University., 2023)
This article aims to elaborate on the Peresean tradition, which is a unique and typical tradition among the Sasak tribe in Lombok, Indonesia. This tradition was held in ancient times to train fighters to fight invaders and beseech for rain. Nowadays, it is used to greet guests or tourists and celebrate national holidays, religious holidays, and traditional days. The present study employed ethnographic approaches. The researcher conducted the study in the West Nusa Tenggara province of Indonesia, specifically focusing on the Sasak tribe. This study result indicates that motivational reasons established from the Peresean tradition are to preserve culture and belief motivation. Meanwhile, the values education implies behind the violence in the Peresean tradition are, first, to strengthen the sense of solidarity and kinship between religions and local community members. Second, the values of such a tradition educate the mentality of sportsmanship to abide by Peresean rules. The third is to educate, in the spirit of courage and toughness, the young generation of the Sasak people in defending and contending for the sake of tribe, religion, and country. The integration between values-education, and people's motivation is the foundation and pillar for preserving the Peresean tradition in the Sasak tribe until today.